Surmounting difficulties to provide home based neonatal care - reflections of community health workers - Abhijit Shrinivas Prabhughate; Pearl Tiwari; Shubhangi Sohoni; Vallaree Anant Morgaonkar; Ajay Gajanan Phatak; Somashekhar Marutirao Nimbalkar; Anagha Anand Mahajani (BMC, 2018)
Abstract Background In India, community health workers' (CHW) effectiveness in providing home-based neonatal care (HBNC) has been well documented. The nature of challenges faced and strategies adopted while providing HBNC services need to be studied in-depth. Methods A qualitative study to understand the challenges faced and strategies used by Sakhis (women CHW) while providing services as part of a HBNC program implemented by a non-profit organization. Data consisted of 20 in-depth interviews and three focus group discussions (FGD) with Sakhis. Results Sakhis negotiated with the community to start working as a CHW. They faced challenges while changing behaviors at individual level and also while bringing about a change in harmful normative practices that increased chances of maternal and neonatal mortality. Managing crises at the time of deliveries and facilitating a safe delivery was the most critical challenge faced by many Sakhis. The key strategies used by Sakhis included: proactively and persistently providing services even when they faced resistance from the woman or her family; evolving contextually suitable counseling techniques and tactics to bring about behavioral change; balancing compliance to traditional practices and promoting HBNC; defying traditional practices and assisting the woman in times of an emergency to save lives. Having on-call support from supervisors and cultivating a good working relationship with health providers facilitated effective service provision by Sakhis. Conclusion CHWs having a strong sense of commitment can develop strategies to address challenges and provide HBNC services effectively if they also have strong supervisory support.